Differential survival of AML subpopulations in NOD/SCID mice - Schubert, Mario; Herbert, Nicolás Nathaniel; Hoffmann, Isabel; Ran, Dan; Singh, Rahul; Eckstein, Volker; Vitacolonna, Mario; Ho, Anthony Dick; Zöller, Margot (Experimental hematology, 2011)
Objective - Leukemia-initiating cells can retrospectively be defined by tumorigenicity in immunodeficient mice and be characterized by surface markers. The latter still being discussed for acute myeloid leukemia (AML), nonobese diabetic/severe combined immunodeficient (NOD/SCID) mice were used to evaluate long-time reconstitution and expansion of AML subpopulations. - Materials and Methods - Bone marrow cells from patients with AML were separated according to CD34 expression, aldehyde dehydrogenase (ALDH) activity, and divisional kinetics in comparison to cord blood−derived CD34+ hematopoietic stem cells, evaluating survival and expansion in NOD/SCID mice. The AML long-term surviving capacity of subpopulations recovered from NOD/SCID mice was confirmed by ex vivo survival. - Results - AML mononuclear cells were detected in bone marrow and spleen of NOD/SCID mice 12 weeks after transplantation. The majority of recovered cells were CD34+ and significantly more CD34+ cells were recovered after application of ALDHbright (high ALDH activity), CD34+, or slowly dividing (PKHbright) than after ALDHdim, CD34−, or fast dividing (PKHdim) cell application. CD123+, CD63+, and CD44v7+ cells were also more abundant after the transfer of ALDHbright or CD34+ AML mononuclear cells. In the spleen, large AML cell clusters were only recovered after ALDHbright, CD34+, or PKHbright cell transfer. Importantly, in secondary long-term in vitro cultures, quite exclusively CD34+ AML mononuclear cells survived and expanded. - Conclusions - Separation of ALDHbright, CD34+, or PKHbright cells enriches for AML long-term surviving capacity, which reside in the CD34+ subpopulation, as rather exclusively CD34+ cells survived and expanded in vivo and ex vivo. Long-term survival capacity may be supported by CD44v7 expression.
Gesehen am 27.10.2022